2012
DOI: 10.3998/ark.5550190.0013.828
|View full text |Cite
|
Sign up to set email alerts
|

Liquid phase organic synthesis of 3,5-disubstituted 1,3,5-thiadiazinane-2-thione derivatives on polyethylene glycol (PEG) support

Abstract: An efficient liquid-phase synthesis of 3,5-disubstituted 1,3,5-thiadiazinane-2-thione derivatives (THTT) is described using soluble polymer support polyethylene glycol (PEG) 5000 via one-pot condensation of PEG-bound free amino acid or PEG-bound tripeptide, a dithiocarbamate and formaldehyde under mild conditions. This procedure affords the target compounds in good yields and high purity with a facile work-up procedure. This synthetic approach has also allowed the efficient preparation of new compounds endowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Thiadiazines, more specifically 3,5-disubstituted thiadiazine-2-thione (THTT), have been studied by the Laboratory of Organic Synthesis (LSO) for more than 20 years [12][13][14][15][16]. Several biological studies in vitro have demonstrated the antiparasitic activity of THTT, which is related to a non-specific high cytotoxicity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Thiadiazines, more specifically 3,5-disubstituted thiadiazine-2-thione (THTT), have been studied by the Laboratory of Organic Synthesis (LSO) for more than 20 years [12][13][14][15][16]. Several biological studies in vitro have demonstrated the antiparasitic activity of THTT, which is related to a non-specific high cytotoxicity [12,13].…”
Section: Introductionmentioning
confidence: 99%